(untitled) (Research, Society and Development, 2020)
This paper aim to explores a philosophical analysis towards the obstacles who experienced by children with cerebral palsy in receiving inclusive education in inclusive schools. This paper based on qualitative research that refers to analytic in philosophy of education as its central method. Reconstructionism as one of the streams in philosophy of education also offer a philosophical response towards the dilemma of inclusive education for children with cerebral palsy through make serious efforts to positioning humanity in inclusive education for children with cerebral palsy. A philosophical response in the form of reframing the concept of inclusive education that held based on humanistic principles point out that inclusive education can be carried out comprehensively. The paper concludes that positioning humanity in providing education for children with cerebral palsy is carried out by aligning various components of education that include teachers, students, places, and time. Thus, positioning humanity in education becomes a holistic foundation in organizing education for all children.